2017
DOI: 10.1038/s41598-017-03112-1
|View full text |Cite|
|
Sign up to set email alerts
|

Noncanonical cell death program independent of caspase activation cascade and necroptotic modules is elicited by loss of TGFβ-activated kinase 1

Abstract: Programmed cell death (PCD) occurs in several forms including apoptosis and necroptosis. Apoptosis is executed by the activation of caspases, while necroptosis is dependent on the receptor interacting protein kinase 3 (RIPK3). Precise control of cell death is crucial for tissue homeostasis. Indeed, necroptosis is triggered by caspase inhibition to ensure cell death. Here we identified a previously uncharacterized cell death pathway regulated by TAK1, which is unexpectedly provoked by inhibition of caspase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…However, HCT116 cells possess RIPK1 (Moriwaki et al , ). A recent report indicates RIPK1 can mediate noncanonical caspase‐ and RIPK3‐independent cell death (Mihaly et al , ). Indeed, inhibition of RIPK1 activity by necrostatin‐1 improved the viability of VPS4A+B‐depleted cells, although only to a limited degree similar to the effect of caspase inhibition by Q‐VD‐Oph (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…However, HCT116 cells possess RIPK1 (Moriwaki et al , ). A recent report indicates RIPK1 can mediate noncanonical caspase‐ and RIPK3‐independent cell death (Mihaly et al , ). Indeed, inhibition of RIPK1 activity by necrostatin‐1 improved the viability of VPS4A+B‐depleted cells, although only to a limited degree similar to the effect of caspase inhibition by Q‐VD‐Oph (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…Although TAK1 prosurvival function in different cell types is well established, there are conflicting studies regarding the mechanism and nature of cell death observed in TAK1 KO cells. In some studies, both RIPK1 and RIPK3 have been shown to promote necrotic and apoptotic cell death in TAK1-deficient cells ( Vanlangenakker et al, 2011 ; Guo et al, 2016 ); however, other studies report that RIPK1, RIPK3 or both are dispensable for the cell death observed in TAK1 KO cells ( Morioka et al, 2014 ; Dondelinger et al, 2015 ; Mihaly et al, 2017 ). Overall, the molecular mechanisms responsible for hyperactivation of the inflammatory immune response seen in conditions of TAK1 inactivation remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms underlying the effect of CtBP2 on DDP chemoresistance. Caspase serves essential roles in cell apoptosis, which is a cellular event considered as programmed cell death (31,32). Caspase-3 is one of the crucial downstream effectors of apoptosis (33).…”
Section: Methodsmentioning
confidence: 99%